The DAO Controversy: The Case for a New Species of Corporate Governance? - Morrison, Robbie; Mazey, Natasha C. H. L.; Wingreen, Stephen C. (Frontiers in Blockchain, 2020)
This paper reviews the recent case of The DAO “hack” in June 2016 and analyzes The DAO's response in its time of crisis, and its implications for corporate and IT governance. There was no human-led governance in The DAO. Instead, The DAO placed its trust in the smart contract they had built together on the blockchain, which became its governance mechanism. The events that follow allow us to see hitherto unobservable organizational behaviors that are unique to trustless organizations, and hence The DAO gives us a glimpse at a new species of corporate governance. This paper explores the implications of these ideas: we propose the emergence of a spectrum of organizations based on the alienation of trust, we consider the economic impact and legality of decentralized autonomous organizations (DAOs), smart contracts, work and job design, and what happens when corporate governance is managed solely by IT governance.